Pondasi Peradaban Pondok Pesantren - i, Khasanuri; Alnizar, Fariz (INC- Islam Nusantara Center, 2023)
The process of religious education in Islamic boarding schools is considered very comprehensive because it does not only transfer knowledge, but transfers values, not only emphasizing theoretical understanding, but practicing worship at the same time and not relying solely on memorizing a series of scientific theories but getting used to the tradition of practice. Rituals also do not only rhetorically promote the concepts of 'sama', tawassuth, and tawazun, but implement them at the practical level of pesantren life. Therefore, up to now Islamic Boarding Schools have become one of the centers for learning Islamic sciences that are most trusted by Muslims. Islamic boarding schools have double power, namely a kyai as the leader of the Islamic boarding school and the Islamic boarding school itself as an educational institution and system. As one of the unique cultural treasures of Indonesian Muslims, Islamic boarding schools have proven to be a barometer of the defense of Muslim morality and are social and religious educational institutions that are capable of changing society in their environment towards the transformation of religious and national values. The basics of Islamic boarding school civilization manifest through the potential and role played by Islamic boarding schools in maintaining their existence and playing an active role in utilizing their potential as educational institutions for the benefit of deepening religious knowledge (tafaqquh fiddin). Proses pendidikan keagamaan di pondok pesantren dinilai sangat komprehensif karena tidak hanya melakukan transfer of konwoledge, akan tetapi transfer of value’s, tidak hanya menekankan pada pemahaman teori, akan tetapi praktik ibadah sekaligus dan tidak hanya mengandalkan hafalan serangkaian teori keilmuan akan tetapi membiasakan diri dalam tradisi praktik ritual juga tidak hanya secara retoris menggalakkan konsep ‘adalah, tawassuth, dan tawazun, akan tetapi mengimplementasikannya dalam tataran praktis kehidupan pesantren. Oleh karenanya hingga sekarang Pondok Pesantren menjadi salah satu pusat belajar ilmu-ilmu keislaman yang paling dipercaya oleh umat Islam. Pondok Pesantren mempunyai kekuatan ganda (double power) yaitu seorang kyai sebagai pemimpin pondok pesantren dan pesantren sendiri sebagai institusi dan sistem pendidikan. Sebagai salah satu kekayaan budaya umat Islam Indonesia yang khas, pondok- pesantren telah terbukti menjadi barometer pertahanan moralitas umat Islam dan merupakan lembaga sosial dan pendidikan keagamaan yang mampu melakukan perubahan masyarakat di lingkungannya ke arah transformasi nilai-nilai keagamaan dan kebangsaan. Dasar-dasar peradaban pondok-pesantren mengejawantahkan melalui potensi dan peran yang dimainkan oleh pondok pesantren dalam mempertahankan eksistensinya dan berperan aktif memanfaatkan potensinya sebagai lembaga pendidikan untuk kepentingan pendalaman ilmu agama (tafaqquh fiddin).